(untitled) (Perner’s Contacts, 2018)
The long-haul operation was perceived as the last bulwark, capturing the respective markets with air services for traditional carrier, however, low-cost air carriers have expanded on long-haul markets recently. In this paper, we compare the competitive weapons of air carriers which operated direct flights on the O-D route Singapore – Melbourne, long-haul low-cost carriers including. The carriers are compared in terms of frequencies, duration of flights, prices and offered classes to passengers. Considering the interlinkages among the carriers, whether based on ownership and/or horizontal cooperation, we reveal two dimensions of competition on the analysed O-D and recommend to tackle more.fragile edges in the triangle of cooperation, competition and coopetiion in the airline industry by regulatory and competition bodies.